Status and influential factors of soil nutrients and acidification in Chinese tea plantations: a meta-analysis - D. Wang; D. Wang; D. Wang; B. Liu; B. Liu; B. Liu; F. Li; F. Li; F. Li; Z. Wang; Z. Wang; Z. Wang; et al. (SOIL)
Knowledge of the status and influential factors of soil nutrients including soil organic matter (SOM), nitrogen (N), potassium (K), phosphorus (P), and acidification is the basis for sustainable management of tea plantations and thus the sustainability of the tea industry. However, a national-level study addressing this topic is lacking. Thereby, we assessed the status, spatial variations, and influential factors of soil nutrients and acidification in China's tea plantations based on 1843 datasets collected from 379 published articles. The results showed that only 40.9 % of the observed tea plantations meet the standards of high-quality tea plantations. Most tea plantations were facing soil acidification, nutrient deficiencies, and imbalance. Furthermore, the status of soil nutrients and pH varied among cultivation zones due to the impacts of location, climate, and soil type. Specifically, tea plantations in the southern zone showed the lowest concentrations of available N, available K, and total K but the highest stoichiometric ratios of soil nutrients (P < 0.05). Management practices (e.g., rotational cycle and fertilization strategies) also significantly shaped the status of soil nutrients and pH. Therefore, applying organic fertilizer, extending the duration of the cultivation cycle, and planting shading trees were recommended to improve soil nutrient availability and balance, as well as to mitigate soil acidification. Specifically, it is recommended to apply K fertilizer to tea plantations in the southern zone and/or at high altitudes.